Etyka w sprzedaży produktów finansowych - Sałek, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2015)
The author examines the existence of unethical behaviour of the employees of financial institutions. This paper is based on studies carried out with the aid of the ‘mystery shopper’ method in Warsaw. Based on the survey, the author wanted to check whether a client is well informed about the real costs of credit and whether a client is asked for an opinion about credit insurance. The outcomes have been compared with the findings of Robert Rogowski published in ʿThe moral dimension of the economic crisis’.